Branched-chain amino acid (BCAA) supplementation enhances adaptability to exercise training of mice with a muscle-specific defect in the control of BCAA catabolism. Issue 5 (4th May 2018) - Xu, Minjun; Kitaura, Yasuyuki; Shindo, Daichi; Shimomura, Yoshiharu
Abstract: Branched-chain α-keto acid dehydrogenase (BCKDH) kinase (BDK) suppresses the branched-chain amino acid (BCAA) catabolism by inactivation of the BCKDH complex. The muscle-specific BDK-deficient (BDK-mKO) mice showed accelerated BCAA oxidation in muscle and decreased endurance capacity after training (Xu et al. PLoS One. 12 (2017) e0180989). We here report that BCAA supplementation overcompensated endurance capacity in BDK-mKO mice after training.